3x - 4y = 7
3x + 2y = -5
When the second equation is subtracted from the first, the resulting equation is

3x - 4y = 7 3x + 2y = -5 When the second equation is subtracted from the first, the resulting equation is -6y = 12 . 3x - 4y - (3x + 2y) = 7 - (-5) 3x - 4y - 3x - 2y = 12 -6y = 12

s

Rating

8

3x - 4y = 7 3x + 2y = -5 When the second equation is subtracted from the first, the resulting equation is -6y = 12 .

3x - 4y - (3x + 2y) = 7 - (-5)

3x - 4y - 3x - 2y = 12

-6y = 12

3x - 4y - (3x + 2y) = 7 - (-5)

3x - 4y - 3x - 2y = 12

-6y = 12

Added 4/22/2015 9:25:19 PM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [4/23/2015 5:15:46 AM]

What is the purpose of a thesis?
It protects you against plagiarism.
It completes your outline.
It states what your paper will prove.
It organizes your first paragraph. **Weegy:** The purpose of a thesis is that it states what your paper will prove. **User:** Select whether the following citation is done correctly:
. . . discovered that cheetahs were the fastest animals on earth (J. Bogart, p.33).
(More)

Question|Asked by alston2013

Expert Answered

Updated 4/24/2015 4:08:09 PM

0 Answers/Comments

35,149,831

questions answered

There are no comments.